The Influence of Interest Rates, Consumption, Investment, Unemployment, and Renewable Energy on Inflation and GDP in Indonesia - Putri Valentine; Rusiadi Rusiadi; Lia Nazliana Nasution (International Journal of Economics, Commerce, and Management, 2024)
This research aims to determine the influence of interest rates, consumption, investment, unemployment and renewable energy on inflation and gross domestic product (GDP) in Indonesia. The variables in this research are Interest Rates, Consumption, Investment, Unemployment and Renewable Energy as independent variables, while the variables Inflation and Gross Domestic Product (GDP) are the dependent variables. The research period is 1993 - 2023. The data analysis technique used is the Simultaneous model, with testing using Eviews 10. Based on the results of the simultaneous analysis, the variables Interest Rate, Consumption and GDP have a positive and significant effect on Inflation. Meanwhile, the Investment Variable does not have a positive and significant effect on Inflation. The Renewable Energy and Inflation variables have a positive and significant effect on GDP. Meanwhile, the unemployment variable does not have a positive and significant effect on GDP.